2000
DOI: 10.1002/1097-0215(20001115)88:4<547::aid-ijc5>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a catalytically inactive H118Y mutant of nm23-H2 suppresses the metastatic potential of line IV Cl 1 human melanoma cells

Abstract: Nm23‐H1 and nm23‐H2 are putative metastasis suppressor genes that encode nucleoside diphosphate kinase (NDPK) A and B. NDPKs form oligomers distributed between soluble and particulate fractions of cells and therefore may exert their effects as either soluble or bound proteins. To determine whether metastasis‐related functions of NDPKs are mediated by their catalytic activity in membrane bound or soluble complexes, we have stably transfected highly metastatic human melanoma Line IV Cl 1 cells with wild‐type and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 17 publications
2
29
0
1
Order By: Relevance
“…The role of nm23-H2 in promoting metastasis is supported by the observation that a catalytically inactive mutant of NDPK-B significantly suppressed the lung metastasis of human melanoma cells in vivo (Hamby et al, 2000). Recent work indicates that activated P2Y 2 R's associate and transactivate vascular endothelial growth factor receptor-2 (VEGFR2) (Seye et al, 2004), directly linking nucleotide receptor activation to established tumour angiogenesis signalling (VEGF-VEGFR signalling).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of nm23-H2 in promoting metastasis is supported by the observation that a catalytically inactive mutant of NDPK-B significantly suppressed the lung metastasis of human melanoma cells in vivo (Hamby et al, 2000). Recent work indicates that activated P2Y 2 R's associate and transactivate vascular endothelial growth factor receptor-2 (VEGFR2) (Seye et al, 2004), directly linking nucleotide receptor activation to established tumour angiogenesis signalling (VEGF-VEGFR signalling).…”
Section: Discussionmentioning
confidence: 99%
“…Nucleoside diphosphate kinase is secreted, despite the lack of a signal sequence, probably via non-classical export as has previously been reported with proangiogenic fibroblast growth factors 1 and 2 (FGF-1 and FGF-2) (Nickel, 2003). The transphosphorylation activity of NDPK-B has been reported to promote the metastatic potential of human melanoma cells (Hamby et al, 2000).…”
mentioning
confidence: 99%
“…Reduced expression of Nm23-H1 promotes metastatic potential in gastric carcinoma to regional lymph node lead to increases in lymphatic metastasis and aberration of transcription regulation (Tomita et al, 2001). Nm23-H2 are less involved in metastasis suppression to than Nm23-H1 homolog (Hamby et al, 2000). The author reported that polyclonal transfectant by Nm23-H2 protein does not initiate metastasis suppressive phenotype to MDA-MB-435 cells, but also the metastatic monoclonal cell lines have high level of Nm23-H2 expression.…”
Section: Differential Expression Of Nm23 Gene Family and Regulationmentioning
confidence: 99%
“…Therefore, we tested the effects of resveratrol on the growth of highly metastatic Line IV clone 1 cultured melanoma cells and on autologous, weakly metastatic Line IV clone 3 cells derived from the same donor. These two cell lines have previously been used in a model system to identify differentially expressed cellular antigens associated with the metastatic phenotype [29,30]. We found that treatment by resveratrol significantly inhibited the proliferation of both cell types.…”
Section: Resultsmentioning
confidence: 95%
“…Notably, these two cell lines were sub-clones of the original Line IV cells established from a single primary melanoma lesion [29,30] whose qualitative differences in metastasis have been demonstrated by subdermal challenge in nude mice. Suppression of proliferation in these two melanoma cells by resveratrol was significantly more pronounced and occurred at a lower dose than what had been previously reported in prostate and breast cancer cells [32,[36][37][38], and also in SK-mel28 melanoma cells [39] although comparable to that found in A375 melanoma cells [39,40].…”
Section: Discussionmentioning
confidence: 99%